Weakness in coping with the multiplication operations among the year 6 pupils in SK RPR Batu Kawa, Kuching, Sarawak and strategies to overcome it / Abang Azhar Abang Malek - Abang Malek, Abang Azhar (2016)
This action research discusses the weakness of Year 6 pupils in SK RPR Batu Kawa, Kuching, Sarawak in mastering multiplication operations and strategies to overcome it In mathematics subject, my pupils' encounter difficulties in mastering multiplication operations, particularly involving the multiplication numbers of two digits with two digits and three digits with two digits without regrouping and regrouping. This research aimed to identify weaknesses in coping with multiplication operations among the Year 6 pupils , to determine the factors that contribute to the weakness of learning the multiplication operation and to identify strategies to overcome weaknesses among the pupils with the multiplication operation in learning mathematics. The research was conducted in SK RPR Batu Kawa, Kuching, Sarawak and involving 30 pupils from Year 6. To obtain data for this study, I utilized two techniques : Pre-Test and Post-Test and two methods : questionnaires and observations. 1 also introduced various strategies to increase pupils' interest and proficiency in multiplication operation such as introducing Smart Table Game, drilling exercise involving multiplication operations and implement various intervention programs. The techniques, methods and strategies introduced by me can improve, help and recover the achievement of pupils in mastering multiplication operation. In the future, teachers can use these techniques and methods to identify factors that cause pupils susceptibility in mastering multiplication operation in school and adopt the strategy that has been practiced by me in this study. This will make learning mathematics more fun, enjoyable and at the same time improve the skills of pupils in solving mathematical problems.